Fire Management in The Boreal Forest of Swedish Sápmi: Prescribed Burning and Consideration of Sami Reindeer Herding During 1920–1970 - Cogos, Sarah; Östlund, Lars; Roturier, Samuel (Environmental Management, 2021)
International audience Forest owners and Indigenous Sami reindeer herders use the same land in northern Sweden for commercial forestry and winter grazing, respectively. Fire management has been controlled by foresters since the late nineteenth century, and Sami herders have had to deal with the effects of both fire suppression and prescribed burning. However, the environmental history of fire management and reindeer herding in Sweden has never been thoroughly investigated. We therefore analyzed written archives in order to understand how reindeer herding was considered in planned burning during the mid-twentieth century, and how the effects of prescribed burning on reindeer herding were interpreted by foresters. We supplemented the interpretation of written sources by including local Sami reindeer herders' insights about prescribed burning. Written records show that reindeer herding was increasingly integrated into the planning process during the twentieth century, yet foresters failed to include important aspects of reindeer herding in their interpretation of the effects of prescribed burning. The Sami consider the effects of burning in terms of fodder availability, opportunities for reindeer to graze the fodder, and any impact on the reindeer's movement patterns and thus herd management. The Sami's historical perspective is essential in order to reconstruct a comprehensive picture of the past, and adapt forestry measures effectively in the future.